Influences of organizational factors on organizational identification and moderating effect of intergenerational workforce in merger and aquisition organizations - Umar Baki, Nordahlia (2016)
Merger and acquisition (M&A) has been a rising trend observed worldwide in the past two decades. M&A refers to organizational restructuring through which an organization integrates with another organization which for business growth and expansion. This study, focusing on employees from M&A organizations, aims to: (i) determine the level of organizational factors (organizational justice and organizational culture); (ii) determine the level of organizational identification; (iii) examine the influence of organizational factors on organizational identification; and (iv) determine the moderating effects of intergenerational workforce on the relationship between organizational factors with organizational identification. Two theories employed in this study were: (i) the Social Identity Theory to provide basic understanding of the factors associated with organizational identification; and (ii) the P-E Fit Theory that explains how ‘person’ and ‘environment’ interacts to each other that may influence organizational identification resulting from variations in organizational factors in the organizations after an M&A. The design of this study was a causal relationship research involving six organizations in which each represents five sectors in the National Key Economic Areas (NKEA) of the 10th Malaysia Plan. A total of 219 respondents participated in this study the sample of which was made through cluster random sampling. The respondents were from the Klang Valley areas of Kuala Lumpur, Petaling Jaya and Putrajaya. The data were collected using a structured set of questionnaires administered through ‘drop-and-pick’ and online survey techniques. Descriptive statistics were used to measure the level of organizational factors and organizational identification. The results indicate that more than half of the respondents perceived moderate level of independent and dependent variables. Using Structural Equation Modeling (SEM) procedures it was found that development, rational and group culture factors significantly contribute to organizational identification and none from organizational justice dimensions. Intergenerational workforce (senior) is found to moderate the relationship between interactional justice, development and group culture with organizational identification. This indicates that Millennials and seniors perceptions on organizational culture and justice practices are different. Therefore, this study suggests that employees should not be viewed as a one homogenous group, instead they are a heterogeneous consisting the Millennials and seniors. The SEM analysis revealed organizational factors explained as much as 62% of the variance in the organizational identification. The implication of this study is that the advanced Social Identity Theory and the P-E Fit Theory were able to capture the moderation effect of the intergenerational workforce on the relationship between the organizational factors on organizational identification. This is a noble contribution to the theories. This study also contributed to the body of knowledge on HRD specifically on the perspectives of organization development and organization behavior which have been less explored from the perspectives of M&A. The study provides a guide for HRD practitioners who must plan interventions in the event of that organizational restructuring. HRD managers should realize that each generation has its own work expectations, organizational values and norms that they hold, therefore, managers should adequately address these organizational factors in their HRD interventions. The study suggested that future research is recommended to include employees from cross-border M&A involving multinational corporations and local companies as this would suggest investigating involving cross-cultural differences. Qualitative studies on organizational identification are suggested in future research.